Experimental analysis of plug shear failure in timber connections with small diameter fasteners loaded parallel-to-grain. (1st July 2021) - Yurrita, Miguel; Cabrero, José Manuel
Highlights: Brittle failure modes may happen in timber connections loaded parallel-to-grain. Plug shear is the main brittle failure in connections with small diameter fasteners. An experimental test campaign has been performed to better understand plug shear. The results analysis allows to identify the main parameters related with plug shear. A comparison of the test results with the existing design models is provided. Abstract: Timber connections with small diameter fasteners that do not go through the whole timber member (such as screws or nails). may fail in brittle or ductile ways. In order to better understand their behaviour, an experimental campaign of tests of connections with small diameter fasteners loaded parallel-to-grain has been performed. The results and analysis of this work provide further information on the role of different parameters in the brittle failure. Existing models are benchmarked against these tests.